Teaching cats in Children’s Literature - Xouplidis, Panagiotis (Journal of Education Culture and Society, 2020)
Aim. The aim of the research is the comparative study of literary cat characters in Children’s Literature texts in Greek and Spanish and their instructive function in the transmission of social stereotypes. Methods. The research subscribes to the field of Literary Animal Studies based on the theory of Children’s Literature (Lukens, 1999) and through the intercultural perspective of Comparative Children’s Literature (O’Sullivan, 2005). Published children’s books from Greece, Spain and Spanish-speaking America were compared using textual analysis methods of Imagology (Beller & Leersen, 2007). Stereotyped variants were identified and organized in categories related to name, physical appearance, gender, behavior, and function of literary cat characters. Results. After examining a corpus of 37 books, 23 in Greek and 17 in Spanish (Argentina, Chile, Colombia, Mexico, Spain), textual analysis findings were compared, organized, and classified by language, country and readers’ age groups to locate that literary cat characters are usually pets or feral, and they remain consistently stereotyped as anthropomorphic and subversive. Cats with seven lives and magical powers are common perceptions, dominating in both cultural contexts, stereotypes extended to strong superstitions about black cats. Conclusions. In Children’s Literature texts, cats are linguistically, literally, and socially defined literary constructs, can have usually human-like features, intercultural influences, and are potentially shaped by intertextual relations. They serve also as a narrative motif for the transmission of social values about non-human animals and the textual familiarization of nonadult readers with society’s cultural stereotypes.